Extragenital Bullous Lichen Sclerosus Treated with Fractional CO2 Laser (FxCO2) and Wet Dressing of Halcinonide Solution: A Case Report - Yuan Y; Wang CJ; Li H (Dove Medical Press, 2022)
Yunyan Yuan, Caroline J Wang, Houmin Li Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of ChinaCorrespondence: Houmin Li, Tel +86 10 88325472, Email lhoumin@sina.cnAbstract: Lichen sclerosis (LS) is an insidious, chronic, relapsing skin disease characterized by atrophic, porcelain-appearing plaques. It usually arises in the anogenital area, but some cases can present in extragenital regions with a variety of presentations, including a bullous variant. Topical corticosteroids are a first-line therapy and are usually the most effective treatment to induce remission of LS. However, there is a subset of patients that does not respond well to topical steroids. Herein, we report an extragenital bullous LS case successfully treated with a fractional CO2 laser (FxCO2) and subsequent wet dressing of halcinonide solution.Keywords: extragenital, bullous, lichen sclerosus, fractional CO2 laser